2020
DOI: 10.1097/aog.0000000000004041
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Foley Catheter for Induction of Labor in Nulliparous Women

Abstract: OBJECTIVE: To assess whether outpatient cervical ripening with a transcervical Foley catheter in nulliparous women undergoing elective labor induction shortens the time from admission to delivery. METHODS: We performed a randomized controlled trial of patients with singleton pregnancies undergoing elective labor induction at 39 weeks of gestation or more with a modified Bishop score less than 5. Women were randomized 1:1 to outpatient or inpatient trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 20 publications
1
45
0
Order By: Relevance
“…Data on route of delivery were available for all eight RCTs (Chen V, Sheehan P. Aust N Zeal J Obstet Gynaecol 2019;59:39-40. doi: 10.1111/ajo.13067). [9][10][11][12][13][14][15] The outpatient group was significantly less likely than the inpatient group to undergo cesarean delivery (21% vs 27%), with a RR of 0.76 (95% CI 0.59-0.98). The RR of cesarean delivery remained significantly lower in the outpatient group when excluding unpublished studies (Chen V, Sheehan P. Aust N Zeal J Obstet Gynaecol 2019;59:39-40. doi: 10.1111/ajo.13067) 15 (RR 0.76, 95% CI 0.58-0.99, n5651) and when including only studies of low risk of bias (RR 0.71, 95% CI 0.53-0.95, n5496).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Data on route of delivery were available for all eight RCTs (Chen V, Sheehan P. Aust N Zeal J Obstet Gynaecol 2019;59:39-40. doi: 10.1111/ajo.13067). [9][10][11][12][13][14][15] The outpatient group was significantly less likely than the inpatient group to undergo cesarean delivery (21% vs 27%), with a RR of 0.76 (95% CI 0.59-0.98). The RR of cesarean delivery remained significantly lower in the outpatient group when excluding unpublished studies (Chen V, Sheehan P. Aust N Zeal J Obstet Gynaecol 2019;59:39-40. doi: 10.1111/ajo.13067) 15 (RR 0.76, 95% CI 0.58-0.99, n5651) and when including only studies of low risk of bias (RR 0.71, 95% CI 0.53-0.95, n5496).…”
Section: Resultsmentioning
confidence: 98%
“…Based on this, we could expect findings that compared outpatient balloon to inpatient balloon plus misoprostol to be similar to our findings, but more research, in the form of RCTs, is needed. Study protocols also differed in their use of Ausbeck 2020 13 Haavisto 2020 14 Rahman 2020 15 Foley or Cook catheters, and the inflation volumes. All studies but one 14 followed intention-to-treat analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Few FDA-indicated cervical ripening methods are available with a safety profile suitable for use outside of the hospital setting. It has been suggested that mechanical methods may be most suited to facilitate outpatient cervical ripening (30,35,36). In comparison to the balloon catheter, Saad et al found that the synthetic hygroscopic cervical dilator allowed for a statistically significant increase in the number of women able to perform their daily activities, and their ability to get some relaxation time and sleep (24).…”
Section: Discussionmentioning
confidence: 99%
“…With the ongoing COVID-19 pandemic, there is an additional incentive to reduce the burden on hospital resourcesand to safely keep patients out of the hospital. Furthermore, publishing on outpatient cervical ripening increased dramatically in 2020 showing a global increase in interest (7,8,16,(35)(36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…Ausbeck and colleagues randomly assigned 126 nulliparous women with a Bishop score <5, at a gestational age ranging from 39 weeks and 0 days through 41 weeks and 6 days, to outpatient overnight CR or inpatient CR with a transcervical Foley catheter. 2 Breech presentation and multiple gestation pregnancies were excluded from the study. The investigators utilized a 16 French Foley catheter and filled the balloon with 30 mL of sterile water.…”
Section: Foley Cathetermentioning
confidence: 99%